Sustainability Accounting: A Comparative Study of Corporate Environmental Disclosures - Gupta, Dr. Ashish; Hashmi , Dr. Sadaf; Prusty , Rita; Khilla , Dr. Gananath; Allamprabhu , Dr.C.Y.; Bareja , Lakshay; Vashisht , Nitish (International Journal of Accounting and Economics Studies, 2025)
Accounting for environmental concerns has been increasingly emerging as a key part of corporate accounting and reporting culture. Environmental information disclosure has been required in many nations. Companies worldwide have also been reporting on the topic voluntarily. Some Indian businesses have tried to show their concern for the environment in their annual reports or through other channels, such as environmental statements or the Internet, in response to growing legal and social demands. However, these disclosures are subjective, non-systematic, and primarily descriptive and positive because there is no formal law, accounting standard, or guideline on the subject topic. Studies on Indian enterprises' environmental reporting have shown that the country's environmental reporting is typically subpar and of low quality to meet the information needs of different report user groups. Sustainability accounting has been popular of late. Several organizations have begun to implement new methods in their annual reports by providing disclosures regarding their primary activities and the impact of the activities on the community. This trend overlaps with the growing pressure from stakeholders on firms to allocate their resources to attain their objectives to realize sustainable development. Sustainability accounting recognizes the significance of financial data and attempts to do so on social and environmental issues. Firms have begun to apply mechanisms and reporting strategies like assurance statements, CSR reports, environmental reports, and even sustainability reports to encapsulate details needed as part of sustainable development initiatives, as no standard or legally accepted reporting scheme exists. The reporting of an organization's environmental performance is the main topic of environmental reporting, which focuses on corporate sector environmental reporting compliance. Emissions of carbon and other greenhouse gases are considered, among other reporting requirements. Since environmental reporting is not required in India, many businesses fail to report information related to this sector. There are significant variations in the caliber and volume of environmental data provided by organizations from different sectors and nations.